Proportioning Study for Low-carbon Sulfate-resistant Concrete by Microbial Corrosion Testing - Wang, Tao; Taniguchi, Osamu; Shibano, Taichi; Araki, Toshio; Koh Yong Jun, Benjamin (Journal of Asian Concrete Federation, 2024)
In addition to water absorption and chloride permeability measurement, sulfate resistance testing by microbial corrosion was conducted on low-W/B concretes made using large amounts of supplementary cementitious materials, including GGBF slag, for use as sewage pipes. The corrosion testing was conducted in a corrosion chamber at 30°C with a H2S concentration of 100 ppm, in which specimens were exposed to the environment under two conditions: one group in the gas and the other partially submerged in circulating sewage water. After exposure for one year, the corrosion rate in the partially submerged phase tended to be 1.3 to 2.9 times higher than in the gas phase. Also, the amount of corrosion was compared, with the corrosion products being examined by EPMA. Exposure to the gas phase and partially submerged phase was thus found to represent the stage of forming monosulfates and dihydrate gypsum and ettringite, respectively. Deterioration was found to proceed at a higher rate as the pH value on the concrete surfaces decreased. Within the range of this study, the addition of silica fume and small-size GGBF slag led to no appreciable effect.